2009
DOI: 10.1007/s12603-009-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

An action research on promotion of healthy ageing and risk reduction of chronic disease: A need assessment study among rural elderly Malays, care givers and health professionals

Abstract: Based on the above findings it is thus, imperative that an appropriate nutritional intervention package and programme be developed so as to help improve nutritional knowledge and subsequently the nutritional status of the rural elderly Malays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Based on the needs assessment exercise in phase 1 reported earlier [10] and the extensive literature review, a nutrition education package consisting of three modes of learning (i.e., a booklet, flipchart and placemats) (Figure 1) was developed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the needs assessment exercise in phase 1 reported earlier [10] and the extensive literature review, a nutrition education package consisting of three modes of learning (i.e., a booklet, flipchart and placemats) (Figure 1) was developed.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the study revealed that older adult subjects had difficulty understanding the food pyramid concept compared with the food plate, as reported in the needs assessment phase [10]. In contrast, health professionals preferred the food pyramid rather than the food plate, probably because they had been trained with the pyramid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equal number of stroke patients had fi nished secondary school and not schooling. Previous study highlighted awareness and knowledge level were associated with socio-economic status and education level in seeking for health related information (Nur' Asyura Adznam et al 2009). However, different information may obtain when study is conducted in a larger scale.…”
Section: Discussionmentioning
confidence: 99%